Hebrews and perfection an examination of the concept of perfection in the "Epistle to the Hebrews - Peterson, David (Cambridge Cambridge University Press, 1982)
The concept of perfection is central to the Epistle to the Hebrews but what is the precise meaning to be attached to the perfecting of Christ and the perfecting of Christians? Is teleioun to be understood in a cultic or ethical sense, or with reference to glorification; or is it employed in a formal sense so that the meaning has to be determined solely from the context? A thorough survey of the background literature suggests to Dr Peterson that it is only the context and, in particular, the object of the verb which can decide its sense on any specific occasion, and it is this method he pursues.
The hermeneutical issues -- The linguistic background -- The perfecting of Christ: the broad perspective -- The perfecting of Christ: his earthly struggle -- The perfecting of Christ: his exaltation -- The perfecting of believers -- Perfection and the purpose of Hebrews -- -- Appendix A: The sinlessness of Christ and his perfecting -- Appendix B: When did Jesus 'become' high priest?
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Bible; Bible -- Theology; Perfection -- Biblical teaching; Perfection -- Biblical teaching; Bible ; Hebrews ; Theology; Perfection ; Biblical teaching